Taxonomical study of social Vespidae at Hutan Simpan UiTM Jengka, Pahang - Siti Khairiyah Mohd Hatta,; Saiyid Jalaluddin Saiyid Shaifuddin,; Ahmad Mustaqim Abd Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2015)
A taxonomy study of social Vespidae family was conducted at Hutan Simpan UiTM Jengka Kem Sri Gading, situated in Pahang Darul Makmur. The objective was to provide an illustrated key for social Vespidae species. The study was conducted from November 2013 until April 2014 by setting up several Malaise traps along the transect lines and the trapped insect were collected once a month. Six traps were used in this study. A total of 286 individuals that belong to Order Tiphiidae, Braconidae, Formicidae, Bethylidae, pompilidae, Ampulicidae, Apidae, Thynnide, Evaniidae, Pelecinidae, Rhopalosomatidae, and Gasteruptidae, has been collected. Thirteen individuals were from subfamily Polistinae, 3 from subfamily Vespinae, and one was from subfamily Stenogastrinae. Six species were identified in which 8 individuals were Parabolybia nodosa, 3 individuals Ropalidia fasciata, 2 individuals of Polistes jokahamae and Vespula flaviceps respectively and 1 each for Vespa tropica and Eustenogaster nigra.